Bees as providers of cultural ecosystem services: case of the Bogotá Botanical Garden, Colombia - Rodríguez-C., Ángela Teresa; García-M., Viviana; Currea-M., Susana (Revista Colombiana de Entomología, 2021)
The purpose of this study was to evaluate the potential of artificial domiciles for solitary bees and thereby explore ecosystem services besides pollination. Artificial modules were installed in three previously selected areas of the Botanical Garden of Bogotá. Weekly monitoring was carried out from June (2017) to August (2019), an exhaustive monitoring every six months and the palynological analysis of 48 samples collected from the modules. Only the Páramo and high Andean Forest module (33.3 %) was colonised by bees (Megachile amparo, Megachile sp., Colletes sp. and Chilicola brooksi). The materials most used as nests were perforated wooden blocks and paper tubes. The emergency rate of incubated nests was higher in Colletes sp., and no order was observed in the emergence of females and males, while in M. amparo the emergence of males was greater. The females of Colletes sp. presented the highest colonization of nests in the study. Pollen analysis of the nests showed that Colletes sp. has a tendency to be oligolectic, while M. amparo and C. brooksi are polylectic. The low number of species that nested in these modules may be indicative of the low potential as a conservation strategy; however, they were useful research tools to understand the habits of species with little or no information. The modules made it possible to have experiential, educational, scientific and aesthetic interactions as forms of cultural ecosystem services, as well as to formulate recommendations to consider the relevance of their implementation.